Sino-Asia agricultural trade and development cooperation: Progress, challenges, and outlook - Mao, Rui; Chen, Kevin Z. (Royal Collins Publishing Company, 2023)
This book includes twelve chapters on agricultural trade and cooperation in Asia, which cover both the review of agricultural development in selected countries and analyses of their development linkages through trade and cooperation. Specific attention has been given to agricultural trade between China and the rest of developing Asia, as China has become the second largest country in agricultural trade, and the unique importance remains for trade partners in Asia due to geographic proximity. Following the outbreak of the COVID-19 pandemic, we also reveal how the global regime of agricultural trade and the Sino-Asia agricultural trade, in particular, has been affected. Overall, the book aims to enhance understanding of the progress, challenges, and outlooks of the Sino-Asia agricultural trade and highlight the room for further cross-country collaborations in agricultural development.